1992
DOI: 10.1091/mbc.3.5.493
|View full text |Cite
|
Sign up to set email alerts
|

Independent pathways regulate the cytosolic [Ca2+] initial transient and subsequent oscillations in individual cultured arterial smooth muscle cells responding to extracellular ATP.

Abstract: Stimulation with extracellular ATP causes a rapid initial transient rise followed by asynchronous periodic oscillations in cytosolic calcium ion activity ([Ca2+]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…However, the contractile responses of these cells were not investigated. By contrast, ATP-induced Ca 2ϩ signaling is better characterized in vascular SMCs (e.g., from the pulmonary artery), where it was found that ATP could induce a series of Ca 2ϩ oscillations (14,21,26). Consequently, the objective of the present study was to characterize the effect of ATP on the Ca 2ϩ signaling…”
mentioning
confidence: 93%
“…However, the contractile responses of these cells were not investigated. By contrast, ATP-induced Ca 2ϩ signaling is better characterized in vascular SMCs (e.g., from the pulmonary artery), where it was found that ATP could induce a series of Ca 2ϩ oscillations (14,21,26). Consequently, the objective of the present study was to characterize the effect of ATP on the Ca 2ϩ signaling…”
mentioning
confidence: 93%
“…The initial rise in [Ca 2+ ] c in response to InsP 3 -generating transmitters has been attributed, traditionally, to a large transient release from the SR (sarcoplasmic reticulum), followed by a secondary, lower sustained increase in [Ca 2+ ] c to above resting levels, the latter depending on extracellular Ca 2+ influx through sarcolemmal Ca 2+ channels [4]. However, re-examination of the changes in [Ca 2+ ] c in single cells within tissues has shown that each cell does not respond to stimulation with a co-ordinated transient and a sustained increase in [Ca 2+ ] c [5][6][7][8]. Rather, at the subcellular level, Ca 2+ signals appear as localized eventsCa 2+ 'puffs' and 'sparks' -which are restricted to a small area of the cell and which comprise the elementary components of the global Ca 2+ response [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…These single-cell [Ca2+li measurements have shown a broad degree of heterogeneity in the calcium response. Mahoney et al (5) have observed that the fraction of cells displaying a primary rise in [Ca2+]i following ligand stimulation is ligand concentration dependent. A lag time, or latency, in the onset of the rise in [Ca2+li following ligand stimulation has been observed in many cell types, including fibroblasts (6), HIT insulinoma cells (7), hepatocytes (8,9), and A10 cells (9).…”
Section: Introductionmentioning
confidence: 99%